The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1111/j.1471-4159.1991.tb08271.x
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive Detection of Glutamate by 1H Nuclear Magnetic Resonance Spectroscopy in Cortical Brain Slices from the Guinea Pig: Evidence for Changes in Detectability During Severe Anoxic Insults

Abstract: 31P and 1H nuclear magnetic resonance spectroscopy (NMR) was used to study the metabolism of intact superfused cortical brain slices during normoxia and anoxia. Attention was focused on quantification of 1H NMR-detected glutamate by a water-suppressed spin-echo method, using N-acetyl aspartate as an internal concentration reference. To quantify the 1H NMR signals, the spin-spin relaxation times and saturation effects were estimated for given metabolites. In addition, absolute concentrations of metabolites were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 31 publications
2
41
1
Order By: Relevance
“…However, factors associated with sample preparation, such as post mortem metabolism and acid extraction, may potentially alter concentrations of metabolites. For instance, it has been shown that acid extraction yields greater glutamate concentration from guinea pig cerebral cortex than is detected by 1 H NMR spectroscopy in situ, possibly as a result of an NMR invisible pool of glutamate (26). Furthermore, the very act of extraction biases the spectra toward metabolites most soluble in the extraction media, and thus small amounts of contamination from control tissue may affect the in vitro results to a greater extent than those obtained in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…However, factors associated with sample preparation, such as post mortem metabolism and acid extraction, may potentially alter concentrations of metabolites. For instance, it has been shown that acid extraction yields greater glutamate concentration from guinea pig cerebral cortex than is detected by 1 H NMR spectroscopy in situ, possibly as a result of an NMR invisible pool of glutamate (26). Furthermore, the very act of extraction biases the spectra toward metabolites most soluble in the extraction media, and thus small amounts of contamination from control tissue may affect the in vitro results to a greater extent than those obtained in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…While it appears that vesicular glutamate may not be detectable by MRS (Kauppinen and Williams 1991), whether or to what extent the vesicular pool of GABA can be detected by MRS is not known. Thus, the 1H-MRS GABA signal arises either mostly or almost entirely from the large cytoplasmic GABA pool in GABAergic neurons under basal conditions.…”
Section: Gabamentioning
confidence: 92%
“…It is important to note that only about 80% of glutamate in brain tissue appears to be observable by 1H-MRS. It is possible that low MRS visibility of glutamate in the vesicular compartment accounts for this finding (Kauppinen and Williams 1991). A small amount of glutamate is present in the extracellular fluid (ECF) of the brain.…”
Section: Glutamate and Glutaminementioning
confidence: 99%
“…Therefore, the glutamate-glutamine cycle may be of relevance to the interpretation of Glx-based results. Second, the glutamate pool within mitochondria and vesicular transporter is not detected by 1 H-MRS, leaving up to 30% of this transmitter unmeasured (De Graaf and BovĂ© e, 1990;Kauppinen and Williams, 1991;Duncan et al, 2014). Third, 1 H-MRS measures cannot distinguish between synaptic and extra-synaptic glutamate (Duncan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%